Pengembangan E-Modul Inventor 2023 Berbasis Android Sebagai Mobile Learning Mata Pelajaran Teknik Pemesinan Di SMK - Hasanuddin Hasanuddin; Achmad Noor Fatirul; Djoko Adi Walujo; Fatkhurrohman Fatkhurrohman (Universitas Darul Ulum, 2023)
This development research aims to find out the results of the development of the android-based Inventor 2023 e-module as mobile learning for the Mechanical Engineering Subject at the Vocational High School level. The development of the production model used is the development of the Dick and Carey model. The results of the validity test data were obtained for R.Count all of the 15 items of questionnaire statement items on all variables in this study yielded values for R.Count > R.Table where the R.Table value was 0.361, so the indicators in these variables can be called valid. For reliability testing, it has a Cronbach's Alpha coefficient that is greater than 0.70 which is equal to 0.818 so that the variables from the questionnaire are reliable. The results of the trial data obtained for content experts were 90.33%, media experts were 84.44%, design experts were 91.61%, peer trials were 90.21%, small group trials were 91.73%, medium group trials of 92.13%, and large/field group trials of 90.04%. With these data, the Inventor 2023 e-module that has been developed falls into very good criteria and is very suitable for use in learning.